Check for false roots too!

Algebra Level 3

The infinite sum of a geometric progression is 1.

If all the terms of this geometric progression are raised to the power of 3, then the sum of all these new terms is equal to 3.

If this time, all the terms of this geometric progression are raised to the power of 2, then what is the sum of all these new terms?


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let the n n th term of the original progression be a n = a r n 1 a_{n} = ar^{n-1} for r < 1 |r| \lt 1 . We are then given that

a 1 r = 1 a = 1 r \dfrac{a}{1 - r} = 1 \Longrightarrow a = 1 - r .

The n n th term of the "cubed" progression will be a 3 ( r 3 ) n 1 a^{3}(r^{3})^{n-1} , and thus we are given that

a 3 1 r 3 = 3 ( 1 r ) 3 = 3 ( 1 r ) ( 1 + r + r 2 ) \dfrac{a^{3}}{1 - r^{3}} = 3 \Longrightarrow (1 - r)^{3} = 3(1 - r)(1 + r + r^{2}) ,

where we substituted in a = 1 r a = 1 - r . Canceling out ( 1 r ) (1 - r) from both sides and simplifying, we find that

1 2 r + r 2 = 3 + 3 r + 3 r 2 2 r 2 + 5 r + 2 = 0 ( 2 r + 1 ) ( r + 2 ) = 0 1 - 2r + r^{2} = 3 + 3r + 3r^{2} \Longrightarrow 2r^{2} + 5r + 2 = 0 \Longrightarrow (2r + 1)(r + 2) = 0 .

Now as we require that r < 1 |r| \lt 1 we must have that r = 1 2 r = -\dfrac{1}{2} , in which case a = 1 r = 3 2 a = 1 - r = \dfrac{3}{2} .

The n n th term of the "squared" progression will be a 2 ( r 2 ) n 1 a^{2}(r^{2})^{n-1} , and so the sum of this progression will be

a 2 1 r 2 = 9 4 1 1 4 = 3 \dfrac{a^{2}}{1 - r^{2}} = \dfrac{\dfrac{9}{4}}{1 - \dfrac{1}{4}} = \boxed{3} .

Guilherme Niedu
Jul 29, 2016

Let's denote the first term as a a and the ratio as q q . We have that:

a 1 q = 1 \frac{a}{1-q} = 1

a = 1-q \fbox{a = 1-q}

a 3 1 q 3 = 3 \frac{a^3}{1 - q^3} = 3

Expanding ( 1 q ) 3 (1-q)^3 and plugging the value of a a :

( 1 q ) 3 ( 1 q ) ( 1 + q + q 2 ) = 3 \frac{(1-q)^3}{(1-q)(1+q+q^2)} = 3

( 1 q ) 2 1 + q + q 2 = 3 \frac{(1-q)^2}{1+q+q^2} = 3

2 q 2 + 5 q + 2 = 0 2q^2 + 5q + 2= 0

q = 2 q = -2 or q = 0.5 q = -0.5 . Since the series is convergent, q < 1 |q| < 1 and, so, q = -0.5 \fbox{q = -0.5} and a = 1.5 \fbox{a = 1.5}

We're looking for:

a 2 1 q 2 = 1. 5 2 1 ( 0.5 ) 2 = 3 \frac{a^2}{1-q~2} = \frac{1.5^2}{1 - (-0.5)^2} = \fbox{3}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...